Next-Generation Sequencing Technologies for Early-Stage Cutaneous T-Cell Lymphoma - Fujii, Kazuyasu; Kanekura, Takuro (Frontiers in Medicine, 2019)
The diagnosis of early stage cutaneous T-cell lymphoma is often difficult, particularly in mycosis fungoides (MF), because the clinical presentation, histological findings, and laboratory findings of MF resemble those of inflammatory skin diseases such as atopic dermatitis, psoriasis, and parapsoriasis en plaque. Furthermore, MF sometimes occurs with or after these inflammatory skin diseases. The current diagnostic criteria heavily rely on clinical impressions along with assessments of T cell clonality. To make a diagnosis of early-stage MF, the detection of a malignant clone is critical. T cell receptor (TCR) gene rearrangements have been detected by southern blotting or polymerase chain reaction for this purpose, but the results of these methods are insufficient. High-throughput TCR sequencing has provided insights into the complexities of the immune repertoire. Accordingly, his technique is more sensitive and specific than current methods, making it useful for the detection of early lesions and monitoring responses to therapy.